Differences between men and women in substance use: the role of educational level and employment status - Ester Teixidó-Compañó; Albert Espelt; Luis Sordo; María J. Bravo; Ana Sarasa-Renedo; B. Iciar Indave; Marina Bosque-Prous; M. Teresa Brugal (Elsevier, 2018)
Objective: To determine differences between men and women in hazardous drinking, heavy cannabis use and hypnosedative use according to educational level and employment status in the economically active population in Spain. Method: Cross-sectional study with data from 2013 Spanish Household Survey on Alcohol and Drugs on individuals aged 25-64 [n = 14,113 (women = 6,171; men = 7,942)]. Dependent variables were hazardous drinking, heavy cannabis use and hypnosedative consumption; the main independent variables were educational level and employment situation. Associations between dependent and independent variables were calculated with Poisson regression models with robust variance. All analyses were stratified by sex. Results: Hazardous drinking and heavy cannabis use were higher in men, while women consumed more hypnosedatives. The lower the educational level, the greater the gender differences in the prevalence of this substances owing to different consumption patterns in men and women. While men with a lower educational level were higher hazardous drinkers [RII = 2.57 (95%CI: 1.75-3.78)] and heavy cannabis users [RII = 3.03 (95%CI: 1.88-4.89)] compared to higher educational level, in women the prevalence was the same. Women with a lower education level and men with a higher education level had higher hypnosedative consumption. Unemployment was associated with increased heavy cannabis use and hypnosedative use in both women and men and with lower hazardous drinking only in women. Conclusions: There are differences between men and women in the use of psychoactive substances that can be explained by the unequal distribution of substance use in them according to educational level. Unemployment was associated with substance use in both men and women.